Children and young people in care until age 26: a must for improved outcomes - Duncan Dunlop (Scottish Journal of Residential Child Care)
Care Leavers have the worst outcomes in our society across most social well-being indicators. This is even more shocking as they are as physically and mentally capable as any other Scot. The Children and Young People Bill1 is an opportunity that can set the legislative framework to address these disparities in outcomes. Towards this end Who Cares? Scotland is leading a campaign to continue to care for our Looked After population until they are 26.The prerequisite for this is that stable loving relationships, which are available for as long as is necessary are the best support for enabling young people to thrive in adulthood. All too often young people are leaving care and supportive trusting relationships too early without the option of staying with or returning to the support those relationships give them. This article explores this fundamental shift in how we perceive and deliver after care more detail.